2017
DOI: 10.1016/j.jcorpfin.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and firm dividend policy—A natural experiment

Abstract: We examine how firms respond to uncertainty around U.S. tax policy changes, namely the individual level tax rate increases set to take effect on January 1, 2011 and January 1, 2013. We provide evidence that firms time the uncertainty in the tax environment and revise their dividend policy to an expected tax increase. We find that firms are likely to initiate their dividends or intensively increase their existing dividend amount one year before the expected tax increase. In addition, in 2012 when there is much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The first one focuses on the firm level uncertainty such as; cash flow uncertainty (Chay & Suh, 2009). The second one focuses on the impact of uncertainties regarding firm environment, caused by event-driven activities, such as political uncertainty (Huang et al, 2015), uncertainty caused by financial crisis of 2008 (Bliss, Cheng, & Denis, 2015), and tax policy changes (Buchanan et al, 2017) on firm payout policy. To add more into this growing body of literature, we adopt a different approach by taking a sample of Chinese non-financial listed firms from 2000 to 2015 to analyse the effect of overall E.P.U.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The first one focuses on the firm level uncertainty such as; cash flow uncertainty (Chay & Suh, 2009). The second one focuses on the impact of uncertainties regarding firm environment, caused by event-driven activities, such as political uncertainty (Huang et al, 2015), uncertainty caused by financial crisis of 2008 (Bliss, Cheng, & Denis, 2015), and tax policy changes (Buchanan et al, 2017) on firm payout policy. To add more into this growing body of literature, we adopt a different approach by taking a sample of Chinese non-financial listed firms from 2000 to 2015 to analyse the effect of overall E.P.U.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, attesting that the firms can withstand the shocks that may prevail as a consequent of economic policy changes. Huang et al (2015), while studying 35 countries, revealed that firms retained more cash during political uncertainty to provide a cushion or preventive measures against future political shocks thus, corroborating the evidence of Buchanan et al (2017) that firms in the United States were less likely to initiate dividends during a period of policy uncertainty.…”
Section: Political Uncertainty and Dividend Policymentioning
confidence: 53%
“…Uncertainty may prevail, particularly when a new president is expected to be elected. Buchanan, Cao, Liljeblom and Weihrich (2017) indicated that policy shocks such as economic and regulatory reforms might affect a firm on the one hand and the benefits of shareholders on the other hand. Hence, this political uncertainty leads a firm to reconsider its financial policies, such as a dividend policy as a precautionary measure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, when a company less investment opportunity it pays a bigger dividend payout from the profit made (Kowalewski, Stetsyuk, & Talavera, 2008;Chen et al, 2019). In the classic study, a company"s net earnings are the critical determinant of dividend changes (Buchanan et al, 2017;Linter, 1956). For this reason, Al-Malkawi (2007) concluded that profitability is an important determinant of the level of profit paid by companies.. Reddy (2006) reveal that paying of dividends show the company profitable.…”
Section: Return On Assetsmentioning
confidence: 99%